Serum Calcium Level among Children with Simple Febrile Seizures Admitted in Chittagong Medical College Hospital - Nahar Bhuiyan, Kamrun; Mosharof Hossain, Mir; Akther, Arifa; Akhter, S M Shamim; Das, Abir; Banik, Rakhi; Choudhury, Zabeen (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Febrile seizure is one of the most common form of seizure occurring in children. Water and electrolyte imbalance occur during acute febrile illness and hypocalcaemia is one of them. It has been found that change in serum calcium might enhance the susceptibility to seizure. This study is aimed to evaluate the association of serum calcium level and febrile seizure among hospitalized children. Materials and methods: This cross-sectional case control study was conducted among 100 hospitalized children of febrile illness in Department of Paediatrics of Chittagong Medical College Hospital, Chattogram, Bangladesh from June 2022 to November 2022. Febrile patients of 6- 60 months of age were enrolled during this study period in two groups, one with seizure and another without seizure. Serum calcium was measured by automated biochemistry analyzer, in a method of Arsenazo-III photometry principle. Collected data were classified, edited, coded and entered into the computer for statistical analysis by using SPSS v23. Statistical significance was defined as p < 0.05 and confidence interval level was set at 95%. Results: The mean age was 20.3±13.1 months in case group and 18.0±12.7 months in control group. Overall male patients were predominant, 29(58.0%) and 30(60.0%) in case and control group respectively. Age, sex, religion, residence and gestational age were not comparable in two groups. The difference of mean birth weight was statistically significant between two groups, 2176.0±293.1 grams in case group and 2328.0±249.9 grams in control group. Most (96.0%) of the patients developed seizures within 7-12 hours of onset of fever. Duration of seizure was 6-10 minutes in half of the patients. Generalized tonic clonic seizure was found to be the predominant seizure type (96%). Cough and cold as presenting features were more in control group than case group (78.0% vs 46.0%). Hypocalcaemia (<8.8 mg/dl) was found significantly higher in case group (50.0% vs 10.0%) with OR (9.0 and 95% CI 3.06-26.44%).Higher mean serum calcium level was significantly documented in control group (8.8±0.9 mg/dl vs 9.4±0.5 m/dl in case and control group respectively). Conclusion: Significant association was found between serum calcium levels and the occurrence of febrile seizures. Low serum calcium levels and occurrence of febrile seizure showed significant association. Presence of low serum calcium levels of less than 8.8 mg/dl was more in patients with febrile seizure. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 46-50